FOXC1 haploinsufficiency due to 6p25 deletion in a patient with rapidly progressing aortic valve disease. Issue 9 (28th June 2017) - Ovaert, Caroline; Busa, Tiffany; Faure, Emilie; Missirian, Chantal; Philip, Nicole; Paoli, Florent; Milh, Mathieu; Macé, Loic; Zaffran, Stephane
Abstract : 6p25 deletion is a rare but well‐known entity. The main clinical features include an abnormal facial appearance, developmental delay, and ocular anomalies. Cardiac anomalies are frequently seen but remain poorly delineated. We describe a 4‐year‐old girl with 6p25.3 deletion, which includes the FOXC1 gene, typical dysmorphic features associated with developmental delay and oculo‐motor anomalies. Aortic valve dysplasia was diagnosed early in life. The cardiac lesion progressed very rapidly between the age of 3 and 4 years requiring aortic valve replacement. Genomic analysis of blood and excised valve tissue showed down‐regulation of FOXC1 but also FOXC2 expression in the diseased aortic valve. This allows us to speculate on the potential role of FOXC1 in aortic valve anomalies.